Bridge substructure and foundation design - Petros P Xanthakos (Prentice-Hall, 1995)
The book presents a systems study of substructure and foundation elements; introduces an independent design methodology demonstrating compliance with AASHTO and other relevant specifications; covers both the allowable stress method and the LRFD approach; and includes a sufficient number of design examples and case studies that show how to obtain credible solutions